Reaching full potential: bioelectrochemical systems for storing renewable energy in chemical bonds. (June 2019) - Su, Lin; Ajo-Franklin, Caroline M
Graphical abstract: Highlights: Bioelectrochemical systems (BESs) electrochemically couple microbes and materials. BESs use electricity or light energy to reduce CO2 to key chemical intermediates. Coupled ion and electron transport underlie these energy conversions. Biophysical tools have discovered some mechanisms for charge transport. Improved understanding and architectures will accelerate BES scalability. Abstract : The growing abundance of wind and solar power has driven interest in utilizing this renewable energy to make chemicals. One of the most efficient and sophisticated frameworks to solar-to-chemical conversion is bioelectrochemical systems that electrochemically couple inorganic catalysts and microorganisms. In particular, microbial electrosynthesis systems and biohybrid systems have used CO2 and electricity or light, respectively, to synthesize organic acids at energy efficiencies that exceed natural photosynthesis. In parallel, new methods have been recently developed to improve the poor mechanistic understanding of these and other bioelectrochemical systems. Deeper knowledge of these underlying molecular processes and creation of new architectures for bioelectrochemical systems are needed to make these promising technologies scale to a commercially relevant level.